Bioprospecção em espécies de Inga (Fabaceae Mimosoideae) - Lima, Nerilson Marques [UNESP] (2015)
The study of natural products as a source of new anticancer agents is very important, because even due to the large amount of existing drugs for the treatment of cancer, has not yet reached an optimal compound that has greater selectivity, fewer side effects, higher potency therapeutic and index of least resistance.One of thefamilies with recognized therapeutic potential is the Fabaceae family, whose chemosystematics show an abundance of flavonoid with broad spectrum of biological activities, including antitumor. Thus, the aim of this study was to isolate and characterize phenolic compounds from fractions obtained of the genus Inga (I. laurina, I. edulis and I. marginata) selected by bioassay cytotoxic and identify metabolites in mixture by HPLC-PDA, HPLC-MS, LC-SPE-TT and NMR Spectroscopy. The chemical composition of these species indicated a wide variety of aromatic acids, flavonoids, tannins and triterpenes. This work describe the characterization of the compounds: lupeol, fatty ester of -amyrin, the olean-18-ene ester and friedelin, vanillic acid, 3,4,5-trimethoxy benzoic acid, gallic acid, gallate methyl, p-coumaric acid, benzoic acid, p-hydroxybenzoic, protocateuico acid, tannic acid, caffeic acid, p-methoxycinnamic acid, p-hydroxybenzoic acid derivative methylated of 4-hydroxybenzoic acid, ferulic acid, myricetin, myricetin-3-Orhamnoside, myricetin-3-O- (2 -O-galoil) - -rhamnopyranoside, apigenin, quercetrin, proanthocyanidin A-2 and procyanidin B, 2-rhamnopyranosyl-3,5-dihydroxyphenyl gallate, 2-rhamnopyranosyl-4,6-dihydroxyphenyl gallateand 4-vinyl-phenol. Through the analysis by HPLC-PDA detected the presence of one anthocyanin from aqueous fraction in five other anthocyanins in the methanolic fraction from seeds of I. edulis. Through the bioassay-guided fractionation was possible to obtain a fraction with high antitumor potential (ED50 = 4.0 mg/mL) that was characterized such a mixture...